A Facile Synthesis of Graphene Quantum Dots via Size-Selective Precipitation and Their Application in GQD-layer Modified DSSC. Issue 1727 (6th February 2015) - Ryu, Jaehoon; Jang, Jyongsik
ABSTRACT: A novel approach to synthesize highly luminescent graphene quantum dots (GQDs) with well-defined sizes was explored based on simple oxidation of herringbone-type carbon nanofibers (HCNFs) and size-selective precipitation. In addition, the upconversion properties of GQD were investigated by applying GQD in working electrode of dye-sensitized solar cells (DSSCs).